Serum steroid profiling by mass spectrometry in adrenocortical tumors: diagnostic implications. Issue 3 (June 2019) - Fanelli, Flaminia; Di Dalmazi, Guido
Abstract : Purpose of review: Liquid chromatography–tandem mass spectrometry (LC–MS/MS), allowing the reliable measurement of large panels of steroids, opened a new era in the characterization of adrenal diseases. This review summarizes the most recent findings on serum steroid profile in benign adrenocortical tumors and provides a focus on the most promising analytical developments. Recent findings: Recently developed LC–MS/MS assays included challenging compounds, providing new knowledge on adrenal steroid secretion. Pioneering studies highlighted the potential of incoming technologies in increasing measurement selectivity and implementing the steroidomic approach. In primary aldosteronism, several studies highlighted the signature of aldosterone-producing adenomas, mainly characterized by secretion of hybrid steroids. The combination of steroid panel and radiological data reached an agreement with adrenal vein sampling-based classification in more than 80% of the cases. The serum steroid profiling in patients with Cushing's syndrome, mainly characterized by reduced androgens and increased 11-dexoycorticosterone in adrenal hypercortisolism, showed a good discriminant power for patients' subtyping (90% correct classification rate). Finally, a selected panel of steroids, including 11-deoxycortisol as the main discriminant compound, was able to achieve a good separation of patients with and without adrenocortical carcinomas. Summary: The constantly evolving serum steroid profiling by MS may improve the diagnosis of different types of adrenocortical tumors.